ANALISIS HUKUM SYARIAH DALAM AKAD KERJASAMA PENGEMBANGAN EKONOMI WISATA HUTAN PINUS - Pebrianto, Reza; Arsyad, Yusri Muhammad; Subaedah; Lawang, Hasanna; Abu Baedah, Said Syafuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The practice of cooperative management of the Bulu Tanah Pine Forest as a form of community-based natural resource utilization requires a study from the perspective of Sharia Economic Law to assess the suitability of the contract, profit-sharing system, and the application of the principle of justice in its implementation. This study aims to analyze the form of contract used in the cooperation and assess its compliance with the pillars and conditions of the contract in the fiqh muamalah. This study uses a qualitative approach with field research. Data collection techniques were carried out through interviews with the management and community involved, direct observation of tourism management activities, and documentation related to activities and cooperation agreements. The data obtained were then analyzed using descriptive-analytical methods to describe the ongoing cooperation practices and assess their compliance with the principles of Sharia economic law. The results of the study indicate that the cooperative practice of the Bulu Tanah Pine Forest tourism management has generally fulfilled the pillars and conditions of the contract, especially in the aspects of the existence of contracting parties, the object of cooperation, and the existence of agreement or willingness between the parties. In addition, the principles of justice and welfare are also evident in community involvement in various tourism economic activities. However, this study also identified several weaknesses, particularly in the administration, recording of cooperation agreements, and transparency in the profit-sharing system. Therefore, although the cooperation agreements implemented are essentially valid under Sharia law, strengthening governance, agreement recording, and transparency systems is needed to ensure that these cooperation practices are more accountable, fair, and sustainable in the future.